How can academic research on UK agri-environment schemes pivot to meet the addition of climate mitigation aims?. (July 2021) - Clements, Jen; Lobley, Matt; Osborne, Juliet; Wills, Jane
Abstract: Agri-environment schemes were introduced in the UK in the 1980s as a response to the widespread environmental damage caused by post-war farming practices. Given such schemes are approaching forty years old, the academic literature is prolific and spans numerous fields including ecology, geography, economics and sociology. This paper reviews the existing literature on such schemes and discusses how it can contribute to benefit the explicit climate mitigation aims of more recent schemes. The focus is upon two key areas: the evaluation of environmental and social outcomes and recurring suggestions for innovation in these schemes. As schemes have been retrofitted to meet new climate aims over the years, moving on from a predominate focus on biodiversity loss, it is argued that academic research has an opportunity to contribute towards the co-design of schemes, with regards to mitigating climate change, especially in light of the key role land use will play in attaining negative emissions. Academic research can inform the development of a new generation of schemes that prioritise carbon sequestration and emission reduction, alongside more traditional biodiversity aims. Highlights: Agri-environment schemes have begun to include climate mitigation aims, this presents an opportunity for research. Academic research can influence the design of schemes, including highlighting options that might provide co-benefit other environmental aims. Research is also needed into where trade-offs and conflicts between diverse aims might arise.